Assessment of Elderlies Sleep Disorders and Different Confronts Methods Among Them - Monir Nobahar; Abas Ali Vafai (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: Sleep is one of the essential needs for human and every disorder in during of sleep causes psychological problem and decreased person>s ability. Although sleep disorders occur in every of ages. Elderly person usually has very problem for satisfied sleep. The aim of this study was to estimate prevalence of sleep disorders and confront methods of those in elderly persons in Semnan city. Methods & Materials: This is a descriptive analytical research. 200 elderly residents of Semnan were selected through rundomical sampling. Sleep disorders was assessment with questioner and interviewer that include of sleep disorders (Dissomnia, Parasomnia) and confront methods (Behavioral, Cognitive, sleep hygiene and drug therapy). Results: Data indicated that prevalence of dissomnia was 67% and prevalence of insomnia was 61% that the most problem were in all stage of sleep (early, intermittent and end). Prevalence of Parasomnia was 29% that more of those (14%) had night terror. In the part of confront methods of sleep disorders, 57% used of behavioral therapy. The most of that (25%) were concentration of the limb before the sleep and 95.5% of them comprehension of cognitive methods. The most of that (26%) were comprehension of effect of age on sleep. 100% of them orientation of sleep hygiene and the most of that (39%) were orientation with 4 choose of sleep hygiene. 20% of them used of drug therapy. Conclusion: Finding above indicate that high prevalence of sleep disorders in elderly in Semnan, need supervised and widespread program for promoting awareness among population about sleep disorders and confront methods of those.